Epidemiology of ROP update – Africa is the new frontier - Gilbert, Clare; Malik, Aeesha N.J.; Nahar, Nazmun; Das, Sanjoy Kumer; Visser, Linda; Sitati, Sarah; Ademola-Popoola, Dupe S. (Seminars in perinatology, 2019)
Several epidemics of blindness due to retinopathy of prematurity (ROP) have been described, with the most recent (the third) occurring in middle income countries in Latin America and Eastern Europe initially, and more recently in the more advanced economies in Asia. In these settings, which are characterized by variation in the quality of neonatal care and inadequate coverage of ROP screening and treatment, larger, more mature infants are affected as well as extremely preterm infants. In 2010 the annual incidence of blindness and visual impairment from ROP globally was estimated to be 32,300, with the lowest incidence in sub-Saharan countries. However, ROP is likely to become an increasingly important cause of blindness in children in sub-Saharan Africa as neonatal care expands unless policies and programmes for control are included at the outset.